Comparative Efficacy of Shunthyadi Taila Nasya Versus Pippalyadi Taila Nasya along with Chitraka Haritaki Systemically in the Management of Allergic Rhinitis – A Case Series - Sivabalaji, K. (Asian Journal of Pharmaceutics (AJP), 2023)
Purpose: Poor lifestyle habituates such as exposure to mist, wind, and dust are the factors responsible for allergic symptoms of the nose and its severity. Allergic rhinitis (AR) is an allergic disease that affects 10–30% of the population. Symptoms include runny nose, sneezing, nasal obstruction, and nasal itching vary from individual, with treatment modalities such as antihistamine, intranasal glucocorticoid, and immunotherapy which need a longer period. In Ayurveda, the symptoms of AR are seen in Nasa Roga under Kshavathu where it gets relief from symptoms and increases the immune system. Hence, Shunthyadi Taila and Pippalyadi Taila nasal drops along with Chitraka Haritaki systemically are administrated. Methodology: Patients aged ≥19 years are included with complaints of watery nasal discharge, paroxysmal sneezing, nasal blockage, or two or more symptoms, with the sample size of 10 in each group and assessed by parameter immunoglobulin (Ig) E level, absolute eosinophil count, and total nasal symptom score (TNSS). Seven days of Marsha Nasya were done with both Taila doses of 4 mL in each nostril along with Chitraka Haritaki internally given in both groups for 30 days of treatment period with pre- and post-assessment. Results: Post-treatment showed significant improvement in TNSS score, eosinophil count, and serum IgE which is statistically significant with P < 0.05. Conclusion: AR is managed by Ayurveda protocol by Nasya and orally mainly controls Vata Kapha dosa. Shunthyadi Taila helps to control acute or sub-acute exacerbation of the symptoms. Chitraka Haritaki has an anti-allergic effect in treating nasal allergies. Hence, both are effective in controlling AR.